2019
DOI: 10.1039/c9ra05933d
|View full text |Cite|
|
Sign up to set email alerts
|

Astragaloside IV (AS-IV) alleviates the malignant biological behavior of hepatocellular carcinomaviaWnt/β-catenin signaling pathway

Abstract: Astragaloside IV (AS-IV) is an active substance isolated from Astragalus membranaceus (Fisch.) Bungede, which has been shown to have pharmacological effects in a variety of cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Scholars have found that astragaloside IV has a certain role in the treatment of cancer in multiple parts of the body. Through the Wnt/β-catenin signaling pathway, astragaloside IV reduces the hepatocellular carcinoma's biologically malignant activity [34] and attenuates 3,4-benzo(a)pyrene increased inflammation caused by macrophages, which led to an abdominal aortic aneurysm [35]. Astragaloside IV is able to enhance the sensitivity of some chemotherapy drugs [36][37][38][39][40][41].…”
Section: Application Of Astragaloside IV In Anti-tumormentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have found that astragaloside IV has a certain role in the treatment of cancer in multiple parts of the body. Through the Wnt/β-catenin signaling pathway, astragaloside IV reduces the hepatocellular carcinoma's biologically malignant activity [34] and attenuates 3,4-benzo(a)pyrene increased inflammation caused by macrophages, which led to an abdominal aortic aneurysm [35]. Astragaloside IV is able to enhance the sensitivity of some chemotherapy drugs [36][37][38][39][40][41].…”
Section: Application Of Astragaloside IV In Anti-tumormentioning
confidence: 99%
“…The search term: TS = ("astragaloside IV"), and the search was from January 1, 1998, to May 31, 2022, with 1011 records. Invalid documents were excluded, including meeting abstracts (34), editorial materials (1), corrections (4), and letters (1). A total of 971 records were retrieved, which were divided into two document types, 891 articles (91.761%) and 80 reviews (8.239%).…”
Section: Data Collectionmentioning
confidence: 99%
“…Astragaloside IV (AS-IV) is a purified natural active component of Astragalus membranaceus, widely used in traditional Chinese medicine [110]. Antioxidant, immunostimulant, and anti-inflammatory properties have been attributed to this plant.…”
Section: Astragaloside IVmentioning
confidence: 99%
“…AS-IV is the main active substance of Astragali Radix, which possesses anticardiovascular disease (Wang Q. N. et al, 2021), liver protection (Liang et al, 2021), antidiabetic nephropathy (Xing et al, 2021), and antitumor activities (Xu et al, 2018). AS-IV exerts antitumor effects on various cancer models, such as lung (Li et al, 2021a), liver (Jiang and Mao, 2019), and colorectal (Ye et al, 2017) carcinomas. In addition, AS-IV can be used in combination with other antitumor drugs and increase the sensitivity of chemotherapy drugs (Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%